Pengaruh Media Sosial Instagram Dan Suasana Cafe (Store Atmosphere) Terhadap Minat Beli (Studi Kasus Coffee Shop Acc Tulungagung) - Nursaidah, Ajeng Sara; Gufron, Mohammad (Fakultas Ekonomi dan Bisnis Universitas Panca Marga, 2024)
This study aims to determine the effect of Instagram social media and cafe atmosphere or store atmosphere on buying interest. The number of samples in this study were 94 respondents with the sampling technique method used was non-probability sampling of purposive sampling type. The test was carried out using the help of the smart PLS 4 application. Which consists of convergent validity test, discriminant validity test, reliability test, determinant coefficient and t test. The results of the study indicate that the results of the t test (partial) Instagram social media and caefe atmosphere (store atmosphere) have a positive and significant effect on buying interest. The results of this study can be used for the development of coffee shop acc Tulungagung in the future. Keyword: Instagram Social Media, Purchase Interest, Store Atmosphere